Rectal temperature and heat transfer dynamics in the eye, face, and breast of broiler chickens exposed to moderate heat stress - Moustafa Yehia; Amani Askri; Ahlem Achour; Jean-Michel Allard Prus; Véronique Ouellet; Nabeel Alnahhas (Poultry Science)
This study aimed to characterize body temperature in finishing broiler chickens and to explore heat transfer dynamics under thermoneutral (TN) and heat stress (HS) conditions. To achieve this, 900 Ross 308 chicks were divided into TN and HS groups, with the HS group subjected to cyclical heat stress (30°C, 45 % RH) from day 28 to day 33 post-hatch. Rectal temperature (Tr) and skin temperature (Ts) at the face (Tsf), eye (Tse), and breast (Tsb) were measured. Tr ranged from 39.1 to 40.6°C under TN and from 40.4 to 43.2°C under HS (Pcondition < 0.001). Core-to-skin temperature gradients were lower under HS (P < 0.0001), indicating reduced heat transfer to the skin. All Ts parameters were higher under HS (P < 0.001), and skin-to-air temperature gradients were also lower (P < 0.0001), reflecting lower heat dissipation. Ts varied significantly across anatomical regions (P < 0.001), and core-to-skin and skin-to-air gradients differed between regions under both conditions (P < 0.001). Strong correlations were observed between Tr and Ts (r = 0.88, 0.89, and 0.92 for Tsb, Tse, and Tsf, respectively), suggesting Ts as a strong predictor of Tr. In conclusion, rectal temperatures in finishing broilers are more variable under HS than under TN. Under HS, some birds continue to exhibit Tr in the physiological range. Under TN, heat is transferred from the core to the eyes at a significantly higher rate than to the face and breast skin. However, the breast skin dissipates heat into the environment at a greater rate than the face and the eyes. These patterns of heat transfer between the core and the skin, and between the skin and the environment are conserved under HS. However, heat transfer rates are significantly reduced leading to increased heat load of the birds. These findings provide further insights into thermoregulation in broiler chickens.